2018
DOI: 10.18203/2349-2902.isj20181596
|View full text |Cite
|
Sign up to set email alerts
|

Clinico pathological aspects of solitary thyroid nodule: a hospital based prospective study

Abstract: Background: Nodular goitre is a common endocrine problem in the world today. Solitary thyroid nodule is defined as the presence of a palpable nodule in the otherwise normal thyroid gland. Solitary nodules are one of the most frequent presentations of thyroid disorder. The aim of this study was to study the incidence and other clinical parameters of solitary thyroid nodules and to correlate between clinical diagnosis and histopathological examination of solitary nodule thyroid.Methods: A prospective study was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
4
1
Order By: Relevance
“…While the majority of our patients also fall within the middle age range (26-35 years), our study has a broader age distribution, including a smaller proportion in the 36-50 years age group (7.2%) and a limited representation of patients over 50 years old (4%). 13 Additionally, the gender distribution in our study shows a reverse trend with 42.4% females and 57.6% males, differing from the female preponderance reported by Rajendranet al (2018) and enkatachalapathyTSetal. 14 Similar to our results, Edwin et al (2020) reported swelling as the predominant symptom in their study, with 50% of patients presenting with this manifestation.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…While the majority of our patients also fall within the middle age range (26-35 years), our study has a broader age distribution, including a smaller proportion in the 36-50 years age group (7.2%) and a limited representation of patients over 50 years old (4%). 13 Additionally, the gender distribution in our study shows a reverse trend with 42.4% females and 57.6% males, differing from the female preponderance reported by Rajendranet al (2018) and enkatachalapathyTSetal. 14 Similar to our results, Edwin et al (2020) reported swelling as the predominant symptom in their study, with 50% of patients presenting with this manifestation.…”
Section: Discussioncontrasting
confidence: 85%
“…Moreover, previous study has linked thyroid hormones to indicators of an adverse metabolic profile, even when they are within the normal range. 12 In comparison to Rajendran et al (2018), our study demonstrates a slightly higher mean age of patients at 48.7 years (SD = 2.11). While the majority of our patients also fall within the middle age range (26-35 years), our study has a broader age distribution, including a smaller proportion in the 36-50 years age group (7.2%) and a limited representation of patients over 50 years old (4%).…”
Section: Discussionmentioning
confidence: 49%
“…There is no inadequate or insufficient cytological smear while a study by Rajendran et al, in 2018 39 observed majority of FNAC reported colloid goiter (84%), 14% showed papillary carcinoma followed by follicular neoplasm (2%).…”
Section: Fine Needle Aspiration Cytologymentioning
confidence: 98%
“…In our study similar to all other studies it is evident that commonest FNAC result is a benign lesion. [12] Present Series Hemithyroidectomy 72 93.3 Subtotal thyroidectomy 14 Total thyroidectomy 14 6.67…”
Section: Fnac Gharib Andmentioning
confidence: 99%
“…Adenomatous goiter are in higher incidences when there is iodine deficient diet. [4] 1980 12 Gary [10] 1972 28.7 Gharib [8] 1984 24 Nagori et al [6] 1992 11 Anantha Krishnan [7] 1993 15.3 Osman Uyar [6] 2017 36.9 S. Rajendran [12] 2018 10 Present Series 2020 10…”
Section: Hpe Reportmentioning
confidence: 99%